2010
DOI: 10.1210/jc.2009-2139
|View full text |Cite
|
Sign up to set email alerts
|

Variable Degree of Growth Hormone (GH) and Insulin-Like Growth Factor (IGF) Sensitivity in Children with Idiopathic Short Stature Compared with GH-Deficient Patients: Evidence from an IGF-Based Dosing Study of Short Children

Abstract: IGF-based GH dosing is clinically feasible in both GHD and ISS patients, although GH dose requirements and auxological outcomes are distinct between these groups. This suggests a degree of both GH and IGF insensitivity in subjects with ISS that requires specific management strategies to optimize growth during GH therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 26 publications
8
98
0
1
Order By: Relevance
“…Variation in the responsiveness to GH therapy implies that individualised dosing of GH according to GH sensitivity may be required in SGA patients. Cohen et al (16,17) showed that targeting higher IGF1 levels by increasing the GH dose in GHD and ISS children resulted in increased change in height in the group of patients who had a GH dosage titrated to achieve IGF1 levels in the upper limit of the normal range compared with those who either had the fixed conventional dose or had received a dosage titrated to achieve IGF1 levels at the mean of a normal range. However, this study only included patients with low IGF1 levels (below K1 SDS), which may exclude those with potential IGF1 resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variation in the responsiveness to GH therapy implies that individualised dosing of GH according to GH sensitivity may be required in SGA patients. Cohen et al (16,17) showed that targeting higher IGF1 levels by increasing the GH dose in GHD and ISS children resulted in increased change in height in the group of patients who had a GH dosage titrated to achieve IGF1 levels in the upper limit of the normal range compared with those who either had the fixed conventional dose or had received a dosage titrated to achieve IGF1 levels at the mean of a normal range. However, this study only included patients with low IGF1 levels (below K1 SDS), which may exclude those with potential IGF1 resistance.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the study on IGF1 titration in GHD and ISS children calculated the difference between measured and target IGF1 SDS using a 20% change in dose for each S.D. unit difference (16,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IGF-1 target chosen affects GH dose requirements, while adjustment of the GH dose to achieve a higher IGF-1 target leads to a faster growth rate. 39,40 However, there are not yet any long-term data regarding whether using a higher serum IGF-1 target will lead to taller adult height.…”
Section: Igf Titration Involves Adjusting the Gh Dose To Keep Igf-1 Imentioning
confidence: 99%
“…52 IGF titration permits adjustment for differences in GH sensitivity between individuals and by gender and by changes in GH sensitivity with age. 20,39,40,53 With standard GH dosing, there is a significant variation in growth rate response and in adult height achieved. More consistently, optimal response might be achieved with individualising treatment.…”
Section: Igf Titration Involves Adjusting the Gh Dose To Keep Igf-1 Imentioning
confidence: 99%